Bacterial infections in cirrhotic patients - Örmeci Baş, Bilge; Çekin, Ayhan Hilmi (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Baş Örmeci B, Çekin AH. Bacterial infections in cirrhotic patients. Turk J Gastroenterol 2019; 30(8): 767-8.